1998
DOI: 10.1046/j.1472-765x.1998.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a kojic acid‐producing fungus capable of using starch as a carbon source

Abstract: A fungal strain (S33‐2), able to grow on cooked starch and produce a substantially high level of kojic acid, was isolated from morning glory flower (Bixa orellana). The fungus was characterized and identified as Aspergillus flavus. The effect of different types of starch (sago, potato and corn starch) on growth of strain S33‐2 and kojic acid production was examined using shake flasks. It was found that strain S33‐2 grew well on all types of starch investigated. However, kojic acid production was highest when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Anchoring ability of dye is critical for DSSCs sunlight harvesting where the efficiency is dependent on dye deposition [42]. Incorporation of also expands theconjugation in KA -and promotes better electron transfer mechanism to the conduction band of TiO 2 , resulting in higher absorption in the visible region [21].…”
Section: Uv-vis Absorption Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Anchoring ability of dye is critical for DSSCs sunlight harvesting where the efficiency is dependent on dye deposition [42]. Incorporation of also expands theconjugation in KA -and promotes better electron transfer mechanism to the conduction band of TiO 2 , resulting in higher absorption in the visible region [21].…”
Section: Uv-vis Absorption Spectramentioning
confidence: 99%
“…Binding of C=O and OH groups to the TiO 2 surface promotes better electron transfer mechanism to the conduction band of TiO 2 . Kojic acid [21,22], a natural pyrone which carries one C=O and two OH groups, is envisaged to have similar properties of natural anthocyanins dyes for its ability to bind with TiO 2 . Kojic acid is a nonhazardous and biodegradable natural product, which was earlier reported for tyrosinase inhibition and colorimetric determination [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The highest kojic acid production of 39.90 g/l in submerged batch fermentation using A. flavus Link 44-1 was obtained when using glucose as a substrate 4 . Using corn starch, rather than glucose, was reported to yield a better production of kojic acid using A. flavus S33-2 7 . Agroindustry byproducts have also been used as a substrate for kojic acid production, the culture of A. flavus number 7 grown on molasses medium successfully produced kojic acid with a maximum level of 53.5 g/l after 8 days of incubation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These results agreed exactly with the early results found by May et al (1931). Kojic acid synthesis only started after growth reached stationary phase and stopped when glucose in the medium was depleted (Kitada et al 1967, Megalla et al1985, Rosfarizan et al 1998, Futamura et al 2001. Rosfarizan& and El-Aasar (2006) reported that the excess concentration of carbon source affects the production of kojic acid and resulted in significant Fermentation medium increase in residual sugar due to the inability of fungi to metabolize high levels of sugar.…”
Section: Effect Of Sugar Concentration On Kojic Acid Productionmentioning
confidence: 99%